Brain uptake of multivalent and multi-specific DVD-Ig proteins after systemic administration. Issue 5 (4th July 2018) - Karaoglu Hanzatian, Denise; Schwartz, Annette; Gizatullin, Farid; Erickson, Jamie; Deng, Kangwen; Villanueva, Ruth; Stedman, Christopher; Harris, Cristina; Ghayur, Tariq; Goodearl, Andrew
ABSTRACT: Therapeutic monoclonal antibodies and endogenous IgG antibodies show limited uptake into the central nervous system (CNS) due to the blood-brain barrier (BBB), which regulates and controls the selective and specific transport of both exogenous and endogenous materials to the brain. The use of natural transport mechanisms, such as receptor-mediated transcytosis (RMT), to deliver antibody therapeutics into the brain have been studied in rodents and monkeys. Recent successful examples include monovalent bispecific antibodies and mono- or bivalent fusion proteins; however, these formats do not have the capability to bind to both the CNS target and the BBB transport receptor in a bivalent fashion as a canonical antibody would. Dual-variable-domain immunoglobulin (DVD-Ig) proteins offer a bispecific format where monoclonal antibody-like bivalency to both the BBB receptor and the therapeutic target is preserved, enabling independent engineering of binding affinity, potency, valency, epitope and conformation, essential for successful generation of clinical candidates for CNS applications with desired drug-like properties. Each of these parameters can affect the binding and transcytosis ability mediated by different receptors on the brain endothelium differentially, allowing exploration of diverse properties. Here, we describe generation and characterization of several different DVD-Ig proteins, specific for four different CNS targets, capable of crossing the BBB through transcytosis mediated by the transferrin receptor 1 (TfR1). After systemic administration of each DVD-Ig, we used two independent methods in parallel to observe specific uptake into the brain. An electrochemiluminescent-based sensitive quantitative assay and a semi-quantitative immunohistochemistry technique were used for brain concentration determination and biodistribution/localization in brain, respectively. Significantly enhanced brain uptake and retention was observed for all TfR1 DVD-Ig proteins regardless of the CNS target or the systemic administration route selected.